Intergenerational status transfer and post-compulsory pathways in a changing education system: a comparison of two Swiss school-leavers' cohorts - Gomensoro, Andrés; Hupka-Brunner, Sandra; Meyer, Thomas (Frontiers in Sociology, 2025)
IntroductionThis study compares the mechanisms of intergenerational occupational status transfer among a subsample of two Swiss school-leaving cohorts (2000 and 2016) that was enrolled in VET programmes at upper-secondary level of education. In particular, we focus on the effect of tracking at the lower-secondary level, which is pronounced in Switzerland and known to play a crucial role for educational and social stratification.MethodsDrawing on data from two cohorts of the TREE1 panel survey, we compare cohort-specific linear regression models that examine overall intergenerational transmission of status and direct as well as indirect or mediating effects of lower-secondary track attendance on (occupational) status attainment. As a measure for analyzing the association between parental and child status, we draw on the recently developed linear hierarchical Occupational Earnings Potential (OEP) scale.ResultsWe find that while the impact of lower-secondary tracking has declined across cohorts, overall intergenerational status transmission remains stable, suggesting that institutional context factors that have changed across cohorts (such as educational reforms and improvements of VET supply) have failed to mitigate intergenerational status transmission and social inequality.DiscussionOur analyses underscore the need for structural policy interventions to enhance educational equity, particularly measures that foster de facto (and not only formal) permeability within the highly stratified Swiss education system.